2008
DOI: 10.1194/jlr.d800017-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive analysis of sterol profiles in human serum by LC-ESI-MS/MS

Abstract: We have developed a highly sensitive and specific method for the analysis of serum sterol profiles. Sterols in 1 ml of dried serum were derivatized into picolinyl esters (3b-picolinate) and analyzed by liquid chromatographytandem mass spectrometry (LC-MS/MS) using the electrospray ionization (ESI) mode. In addition to cholesterol, 19 cholesterol precursors, cholestanol, campesterol, sitosterol, and sitostanol were identified simultaneously. Quantitative analyses for the picolinyl esters of 11 available sterols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
143
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(145 citation statements)
references
References 41 publications
2
143
0
Order By: Relevance
“…Alkali-treated lipid extract was dried, resuspended in 1 mL tetrahydrofuran (THF)/methanol/ water (2:1:2, v/v/v) containing 0.1% formic acid, and used for LC-MS/MS analyses of sphingolipids and SG. FS was analyzed by LC-MS/MS after picolinyl esterification according to Honda et al (2008).…”
Section: Preparation Of Sphingolipids and Sterolsmentioning
confidence: 99%
“…Alkali-treated lipid extract was dried, resuspended in 1 mL tetrahydrofuran (THF)/methanol/ water (2:1:2, v/v/v) containing 0.1% formic acid, and used for LC-MS/MS analyses of sphingolipids and SG. FS was analyzed by LC-MS/MS after picolinyl esterification according to Honda et al (2008).…”
Section: Preparation Of Sphingolipids and Sterolsmentioning
confidence: 99%
“…Briefly, 50 ng of coprostanol was added to 5 L of serum as an internal standard, and alkaline hydrolysis in 1 N ethanolic KOH and derivatization to the picolinyl esters were carried out 14) . Then the picolinyl ester derivatives of the sterols were quantified by LC-MS/MS 15) . Coprostanol, a compound almost nonexistent in normal human serum, was used as an internal standard, because coprostanol and the sterols of interest to us should be lost to the same extent during the quantification process due to their structural similarity.…”
Section: Determination Of Sterol Concentrationsmentioning
confidence: 99%
“…In general, ESI is not the best ionization method for neutral steroids because of its poor ionization efficiency. However, our recent study demonstrated that the derivatization of monohydroxysterols into picolinyl esters markedly enhanced the ionization efficiency in the ESI process, and the method was much more sensitive than the assay of native monohydroxysterols by LC-APCI-MS/MS (23). In this study, we have applied our derivatization method to dihydroxy-and epoxysterols.…”
mentioning
confidence: 99%